Capillary electrophoresis fingerprinting coupled with chemometrics to evaluate the quality consistency and predict the antioxidant activity of Sanhuang tablet as part of its quality control. Issue 23 (2nd October 2014) - Wang, Yan; Sun, Guoxiang; Liu, Zhongbo; Liu, Yingchun; Gao, Yaning; Zhang, Jianqing; Ji, Zhengchao; Chen, Xinxin
<x xml:space="preserve">Abstract</x> A capillary electrophoresis fingerprint was constructed for Sanhuang tablet, a Chinese traditional patent medicine, that was commonly used in clinical practice, where the isosceles trapezoid method was first applied for the optimization of background electrolyte solution, and the resolution index was performed to assess the experimental conditions; furthermore, a novel linear quantitative fingerprint method was established for accurate qualitative and quantitative discrimination of the test samples from diverse commercial brands. The fingerprint analysis coupled with quantitative determination of two components was employed to elucidate that the quality consistency of the products was relatively good within one manufactory, but poor among different companies for the 30 batches of samples. In addition, the fingerprint–efficacy relationship between chemical components and antioxidant activity in vitro was investigated using partial least squares analysis, and the calibration and prediction of the antioxidant activity of the selected samples via fingerprint data were presented with the desired results. This work illustrates that the proposed fingerprint analysis based on linear quantitative fingerprint method can be applied for the quality evaluation of traditional Chinese medicine and herbal preparations as part of their quality control, and the constructed mathematical model is particularly suitable for depicting the fingerprint–efficacy relationship.